P125 IL-36 axis is an emerging therapeutic target in psoriatic arthritis synovial tissue. (March 2019) - Boutet, M-A; Nerviani, A; Lliso-Ribera, G; Goldmann, K; Lewis, M; Pitzalis, C
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: The IL-36 family of cytokines includes three agonists (IL-36α, β and γ) and two established or hypothetical antagonists (respectively IL-36Ra and IL-38). IL-36 agonists are pro-inflammatory cytokines highly expressed in skin, cleaved and activated by neutrophil proteases and involved in the pathogenesis of psoriasis. They have only limited effect in driving synovial inflammation in rheumatoid arthritis (RA) but little is known about the expression and biologic functions of the IL-36 axis in synovial tissue of psoriatic arthritis (PsA). Objectives: In this study, we aimed to investigate the expression pattern and role of the IL-36 cytokines in early treatment-naïve PsA synovium in comparison with RA. Methods: Synovial tissue samples were collected from patients with early (disease duration <12 months) RA and PsA DMARDs (Disease Modifying Anti-Rheumatic Drugs) and steroids-naïve. All patients underwent an ultrasound-guided synovial biopsy before starting the treatment and after six months of treatment with conventional DMARDs. The expression of IL-36 family members was investigated in synovial tissue at gene level by RNA-Sequencing (87 RA, 15 PsA), at protein level by immunostaining (20 RA, 26 PsA) and in plasma by ELISA (22 RA, 38 PsA). RA and PsA-fibroblasts-like-synoviocytes (FLS) were treated in vitro to assess their response to IL-36 stimulation. Results: Gene and protein expression of IL-36 agonists was comparable between RA and PsA synovial tissue; conversely, the antagonists were significantly lower in PsA compared to RA. Accordingly, the agonists/antagonists ratio was considerably higher in PsA synovium, also characterized by a strong neutrophil-signature, suggesting an activation of the IL36 pro-inflammatory pathway. Among the immune cells infiltrating the PsA synovium, macrophages (CD68+) and plasma cells (CD138+) were the primary IL36α-expressing cells. At baseline, the synovial expression of IL-36α was significantly higher in PsA patients who did not respond to DMARDs treatment at 12 months; this differential synovial expression of IL-36α between responders and non-responders was also maintained at six months. In keeping with this observation, we showed that treatment with DMARDs did not reduce the expression of IL-36 in PsA cells in vitro . Finally, we observed that PsA-FLS produced significantly higher levels of IL-8 upon stimulation with IL-36α in comparison with cells isolated from RA patients. Conclusions: The impaired balance between IL-36 agonists and antagonists observed in PsA synovial tissue might contribute to the persistent inflammation characterising the diseased tissue. The exogenous replacement of the IL-36 antagonists may be a novel promising therapeutic target for PsA patients. Disclosure of Interest: None declared.